HALAL MARKETING AND FINANCIAL PERFORMANCE: STUDY IN COSMETIC COMPANIES IN INDONESIA - Pratisti, Cahyani; Maryati, Sri (KINERJA, 2019)
This study aims to prove the empirically relationship between halal marketing (halal labelling and hijabista celebrity endorsement) with financial performance. The independent variable is halal labeling and hijabista celebrity endorse, while the dependent variable is financial performance. This research was conducted in Indonesia, spread across five cities such as: Jakarta, Lampung, Bali, West Sulawesi, and Aceh with samples of PT. Paragon Technology and Innovation and PT. Sari Ayu., Tbk. Survey methods and 51 questionnaires used in this research. The result shows that halal labelling has no effect on financial performance, while hijabista celebrity endorse has an effect on financial performance.Keywords: halal labeling, hijabista celebrity endorse, and financial performance